2001
DOI: 10.1046/j.1365-313x.2001.01129.x
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid permeases in developing seeds ofVicia fabaL.: expression precedes storage protein synthesis and is regulated by amino acid supply

Abstract: SummaryFull length cDNAs encoding three amino acid permeases were isolated from seed-speci®c libraries of Vicia faba. The predicted proteins VfAAP1, VfAAP3 and VfAAP4 share up to 66% identity among themselves. Functional characterization of VfAAP1 and VfAAP3 in a yeast mutant showed that these permeases transport a broad range of amino acids. However, VfAAP1 had a preference for cysteine and VfAAP3 for lysine and arginine. VfAAP1 was highly expressed in cotyledons at early developmental stages and moderately i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(118 citation statements)
references
References 59 publications
4
111
0
2
Order By: Relevance
“…It could be shown that the expression of the amino acid transporter in seeds precedes the expression of the storage protein AtS1 in Arabidopsis (11). A similar increase in the expression of a legume amino acid transporter has been shown recently in Vicia faba (12). In pea it has been demonstrated that PsAAP1 is expressed in the transfer cell layer of cotyledons and might be responsible for taking up amino acids released from the seed coat (13).…”
supporting
confidence: 62%
“…It could be shown that the expression of the amino acid transporter in seeds precedes the expression of the storage protein AtS1 in Arabidopsis (11). A similar increase in the expression of a legume amino acid transporter has been shown recently in Vicia faba (12). In pea it has been demonstrated that PsAAP1 is expressed in the transfer cell layer of cotyledons and might be responsible for taking up amino acids released from the seed coat (13).…”
supporting
confidence: 62%
“…Leustek and Saito, 1999;Kopriva, 2006). Directed transport of Cys across the organelle envelopes was simply assumed and thought to be performed by transport proteins with limited specificity, such as the transporters involved in the uptake of amino acid at the plasmalemma (Miranda et al, 2001;Fischer et al, 2002). However, direct evidence for the transport of Cys between cytosol and compartments is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…The switch to an active uptake system occurs rather late in development and is based on enhanced levels of AAP1 (an amino acid permease) and PTR1 (a peptide transporter) in the embryo proper (Miranda et al, 2001). This transport system appears to be controlled by assimilate availability (Bennett and Spanswick, 1983).…”
Section: The In Vivo Steady-state Level Of Free Amino Acids In the Enmentioning
confidence: 99%